Conceptual principles of ecological restoration - Madroñero-Palacios, Sandra (2024)
This review article sought to publicize the evolution since its inception of the conceptualization of ecological restoration, establishing the different agreements and international conferences that guide the management and implementation of said area, likewise, the conceptual bases of the subject are raised, establishing the importance, applicability and existing differences in relation to concepts such as rehabilitate and recover. For this, an organized search for information was developed, allowing the systematization of the documentation through the application of five phases, the categories of analysis taken into account were the regulations and international agreements on ecological restoration and the conceptualization that supports it. The main results highlight the importance of the different international summits, goals, and challenges that have contributed to the development and management of ecological restoration, it was possible to conceptually identify the existing types of restoration, their characteristics, and differences. The existing difficulties in achieving the goals that have been set worldwide in terms of restoration processes are established. Among the main conclusions, the importance of ecological restoration in improving the conditions of ecosystems is highlighted, which allows them to restore their components, structure, and function, likewise, ecosystems that have suffered intense disturbances that manage to substantially transform their characteristics. they have the option of being rehabilitated or recovered in which it is not possible to bring it to the pre-disturbance ecosystem but it allows to restore certain functions for the sustainability of the ecosystem and human well-being.